Microbial electrochemical degradation of lipids for promoting methane production in anaerobic digestion. (February 2022) - Dong, Haiquan; Yue, Liangchen; Cheng, Jun; Xia, Rongxin; Zhou, Junhu
Highlights: Microbial electrochemical degradation was proposed to anaerobic digestion of lipids. The beta-oxidation of lipids was strengthened with an applied voltage. The electron transfer rate constant at 0.8 V was 14.4-fold that at 0 V. Energy conversion efficiency in methane production increased to 60.1% Abstract: In order to solve problems of low methane production from lipids in anaerobic digestion, microbial electrochemical degradation was proposed to promote methane yield of glycerol trioleate (a typical lipid component of food waste). The beta-oxidation of lipids was strengthened with an applied voltage to promote electron transfer and anaerobic digestion. SEM images showed that a lot of spherical and rod-shaped microbes adhered to electrode surfaces. Cyclic voltammetry showed that electron transfer rate constant at 0.8 V was 14.4-fold that at 0 V. Three-dimensional fluorescence spectroscopy showed that small organic degraded molecules were used more efficiently in anaerobic digestion. The methane yield of glycerol trioleate increased to 791.6 mL/g-TVS (at 0.8 V), while methane production peak rate increased to 26.8 mL/g-TVS/d with a shortened peak time to 24th day. The overall energy conversion efficiency in methane production increased from 53.6 to 60.1% due to microbial electrochemical degradation of lipids.